Rereading the Concept of Nusyūz in Islamic Marriage Law with Qira'ah Mubādalah - Khoirotin Nisa'; Muslih Muslih; Abu Hapsin (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
Islam exists in order to uphold justice. Likewise with families, where there are often unfair relationships between husband and wife, there are so many obstacles which can threaten the harmony of marriage. So far the issue of nusyūz is often connected to the wife and the Compilation of Islamic Law (KHI) conﬁrms this. How Islamic law regulates nusyūz and how the perspective of qira'ah mubādalah about this nusyūz is are the main questions of this study. This study uses normative legal research method with descriptive technique. Data collection was carried out by literary study and then they were analyzed qualitatively by the deductive method. The results of this study are as follow: Nusyūz according to Islamic law (KHI) is conceptualized as a wife's disobedience to her husband, such as reluctance to have intercourse, surly in front of her husband, leaving the house without the husband's permission and others which make the husband dislike. If nusyūz occurs then it is resolved by: giving advice, separating beds, and hitting. Mubādalah as a method of interpretation of texts which is reciprocal, in terms of family relations between husband and wife, deﬁnes nusyūz as disobedience to household commitments so it applies to husband and wife. Nusyūz settlement by beating is considered as an act of violence so it should not be done. Inviting reconciliation to return to commitment is the best way according to QS. An Nisa': 128.